2022
DOI: 10.1097/brs.0000000000004326
|View full text |Cite
|
Sign up to set email alerts
|

Insurance Type is Associated with Baseline Patient-Reported Outcome Measures in Patients with Lumbar Stenosis

Abstract: Prior research suggests that sociodemographic factors influence patient-reported outcome measures (PROMs). By investigating PROMs from patients with lumbar spinal stenosis, we found that insurance type is associated with different baseline PROMs. These findings have broad ranging implications for research and healthcare policy, especially when using PROMs as measures of value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…Patients included in this investigation were identified through a query of the Research Patient Data Registry (RPDR) at our institution. In brief, the RPDR is a utility that pools medical and billing information for all patients in our system and has been utilized in numerous prior works [19][20][21][22] . We included adults who underwent rotator cuff repair, lumbar discectomy, lumbar fusion, total knee arthroplasty (TKA), total hip arthroplasty (THA), open reduction and internal fixation (ORIF) of ankle fracture, ORIF of distal radial fracture, or anterior cruciate ligament (ACL) reconstruction between January 1, 2018, and March 31, 2022.…”
Section: Methodsmentioning
confidence: 99%
“…Patients included in this investigation were identified through a query of the Research Patient Data Registry (RPDR) at our institution. In brief, the RPDR is a utility that pools medical and billing information for all patients in our system and has been utilized in numerous prior works [19][20][21][22] . We included adults who underwent rotator cuff repair, lumbar discectomy, lumbar fusion, total knee arthroplasty (TKA), total hip arthroplasty (THA), open reduction and internal fixation (ORIF) of ankle fracture, ORIF of distal radial fracture, or anterior cruciate ligament (ACL) reconstruction between January 1, 2018, and March 31, 2022.…”
Section: Methodsmentioning
confidence: 99%
“…Potentially eligible patients were initially identified through a query of the Research Patient Data Registry (RPDR), an internal database that links billing and electronic health records information to aggregate demographic and clinical information from patients treated through our health system. RPDR has been utilized previously in numerous investigations within the spine field [17][18][19] and outside of it. 20,21 Our RPDR query identified 1261 unique adult patients from January 2015 to January 2022 who underwent lumbar fusions for an indication of isthmic or degenerative spondylolisthesis.…”
Section: Participantsmentioning
confidence: 99%
“…The correlation between an individual’s SES, treatment options, and PROs is poorly understood. Crawford et al revealed that Medicaid patients with lumbar spinal stenosis had systematically worse baseline PROs when compared to Medicare or private insurance [ 10 ]. It has also been shown that lower SES can predict worse outcomes in lumbar spine surgery [ 11 ].…”
Section: Introductionmentioning
confidence: 99%